Highly Stretchable Hydrogels as Wearable and Implantable Sensors for Recording Physiological and Brain Neural Signals. Issue 16 (31st March 2022) - Liang, Quanduo; Xia, Xiangjiao; Sun, Xiguang; Yu, Dehai; Huang, Xinrui; Han, Guanghong; Mugo, Samuel M.; Chen, Wei; Zhang, Qiang
Abstract: Recording electrophysiological information such as brain neural signals is of great importance in health monitoring and disease diagnosis. However, foreign body response and performance loss over time are major challenges stemming from the chemomechanical mismatch between sensors and tissues. Herein, microgels are utilized as large crosslinking centers in hydrogel networks to modulate the tradeoff between modulus and fatigue resistance/stretchability for producing hydrogels that closely match chemomechanical properties of neural tissues. The hydrogels exhibit notably different characteristics compared to nanoparticles reinforced hydrogels. The hydrogels exhibit relatively low modulus, good stretchability, and outstanding fatigue resistance. It is demonstrated that the hydrogels are well suited for fashioning into wearable and implantable sensors that can obtain physiological pressure signals, record the local field potentials in rat brains, and transmit signals through the injured peripheral nerves of rats. The hydrogels exhibit good chemomechanical match to tissues, negligible foreign body response, and minimal signal attenuation over an extended time, and as such is successfully demonstrated for use as long‐term implantable sensory devices. This work facilitates a deeper understanding of biohybrid interfaces, while also advancing the technical design concepts for implantable neural probes that efficiently obtain physiological information. Abstract : A strategy is proposed using microgels as large crosslinking centers in hydrogel networks to modulate the tradeoff between modulus and fatigue resistance/stretchability. The prepared hydrogels can be used to obtain physiological signals, record the local field potentials in brains, and transmit signals through injured peripheral nerves. The appropriate performances lead to negligible foreign body response and signal attenuation with time.